The mechanism of interaction between an author and the publisher of a scientific journal: problems and solutions - I. D. Kotlyarov (Библиосфера, 2011)
The paper presented contains the analysis of the main problems existing in interaction between a researcher and a scientific journal in Russia. These problems include publication charges and reviewing process. Ways to solve these problems are proposed.